2023
DOI: 10.1021/acssuschemeng.3c00593
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Amino Acid with THF for the Synergistic Promotion of CO2 Hydrate Micro Kinetics: Implication for Hydrate-Based CO2 Sequestration

Abstract: CO 2 capture and sequestration are broadly recognized as the most effective technology for reducing CO 2 emissions and mitigating global climate change. In this regard, hydrate-based CO 2 sequestration (HBCS) has been proposed as an effective method for long-term safe and stable CO 2 sequestration. It is a promising technology for reducing the concentration of CO 2 in the atmosphere and achieving carbon neutrality. However, one major challenge related to HBCS technology is the lack of understanding of how to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…It was only after t c when a pronounced pressure drop was observed that H 2 started to be consumed and trapped in the H 2 –THF hydrate cages. Such behavior was also identical to the CO 2 –THF hydrate system (below 2.0 mol % THF) …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…It was only after t c when a pronounced pressure drop was observed that H 2 started to be consumed and trapped in the H 2 –THF hydrate cages. Such behavior was also identical to the CO 2 –THF hydrate system (below 2.0 mol % THF) …”
Section: Resultsmentioning
confidence: 90%
“…Continuous high driving force for H 2 –THF hydrate formation may be needed only when H 2 gas uptake is significantly high, and such a barrier can be potentially overcome by continuously injecting H 2 during the formation process. Such tuning of THF concentration on the THF–CO 2 hydrate has been recently observed and systematically investigated in the study of Liu et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas composition after completion of the formation was analyzed by visual experiments and gas chromatography. The formation model of R134a/CO 2 hydrate under SDS conditions was summarized . R134a begins to form hydrate from the gas phase, while the CO 2 hydrate is formed from dissolved gas at the gas–liquid interface (hydrate precipitation may also occur in the liquid phase).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of hydrate thermodynamic accelerators such as tetrahydrofuran (THF), cyclopentane (CP), and DIOX could induce the formation of more CO 2 sII hydrates, which could absorb more gas molecules, , and the phase equilibrium curve shifted to the high temperature and low-pressure region further shortening the induction time. , Fan et al compared the separation effect of tetrabutylammonium fluoride (TBAF) with tetrabutylammonium bromide (TBAB) and tetrabutylammonium chloride (TBAC) for CO 2 /CH 4 gas mixtures and found that the addition of TBAF not only allowed the formation of hydrates at close to room temperature but also the improved efficiency of the gas mixture separation by TBAF was better than that by TBAB or TBAC. Sun et al conducted a systematic experimental study on the separation of CH 4 /N 2 in tetrahydrofuran (THF) solution by using the hydrate technology.…”
Section: Introductionmentioning
confidence: 99%